2018
DOI: 10.1021/acsphotonics.7b01337
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Optical Device with Tunable Transparency Using Colloidal Core/Shell Nanoparticles

Abstract: Suspended particle devices (SPDs) adapted for controlling the transmission of electromagnetic radiation have become an area of considerable focus for smart window technology due to their desirable properties, such as instant and precise light control and cost-effectiveness. Here, we demonstrate a SPD with tunable transparency in the visible regime using colloidal assemblies of nanoparticles. The observed transparency using ZnS/SiO 2 core/shell colloidal nanoparticles is dynamically tunable in response to an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
(62 reference statements)
0
21
0
Order By: Relevance
“…Based on the reflective intensity of green composite films with different opal thicknesses, their color space coordinates were determined in Figure S11a. We found that the color purity was enhanced from 0.55 to 0.82 following the increase in the colloidal crystal thickness, as shown in Figure S11b. In transmission spectra (Figure b), the intensity decreased as film thickness increased, which was not significant and occurred gradually.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Based on the reflective intensity of green composite films with different opal thicknesses, their color space coordinates were determined in Figure S11a. We found that the color purity was enhanced from 0.55 to 0.82 following the increase in the colloidal crystal thickness, as shown in Figure S11b. In transmission spectra (Figure b), the intensity decreased as film thickness increased, which was not significant and occurred gradually.…”
Section: Resultsmentioning
confidence: 80%
“…To prepare core−shell nanospheres, the ZnS nanoparticles were synthesized by homogeneous nucleation and growth of proportional ionic precursors as described in a previous report. 46 We demonstrate that the size of ZnS particles can be controlled from 80 to 150 nm in diameter to secure structural colors in a visible region, in which a polyvinylpyrrolidone (PVP) was utilized as a stabilizer. Aggregation was circumvented, and silica precursors were easily deposited onto the ZnS core particles.…”
Section: T H Imentioning
confidence: 99%
“…Synthesizing core-shell electrochromic PCs to construct composite smart windows not only improves the electrochromic performance of materials, but also broadens the functionality of smart windows. Han et al [110] designed electrochromic devices containing ZnS-SiO 2 and a-Fe 2 O 3 -SiO 2 core-shell PCs, respectively, and verified that the transparency of the devices increased with the increase in applied voltage (Fig. 7).…”
Section: Core-shell Pcsmentioning
confidence: 86%
“…Synthesis of Core-Shell ZnS-SiO 2 Nanoparticles: ZnS nanoparticles were prepared by co-precipitation of zinc acetate dihydrate and sodium sulfide following the method described in previous report. [44] For preparing silica shell on ZnS nanoparticles, 20 mL of 2 wt% ZnS nanoparticles in ethanol was added to 20 mL of ethanol with 4 mL of ammonium, and deionized water (DI) (8 mL), which was stirred vigorously for 15 min. Then, for the amine functionalization, 2 mL of TEOS and APTES precursor with the volume fraction ratio of 99:1 (TEOS:APTES) was dissolved in 40 mL of ethanol, and slowly dropped to the solution by an automatic syringe pump for 2 h to form the functionalized silica shell.…”
Section: Methodsmentioning
confidence: 99%